The effect of adalimumab on key drivers in the pathogenesis of psoriasis. (1st March 2014) - Hendriks, A.G.M.; van der Velden, H.M.J.; Wolberink, E.A.W.; Seyger, M.M.B.; Schalkwijk, J.; Zeeuwen, P.L.J.M.; de Jong, E.M.G.J.; Pasch, M.C.; van Erp, P.E.J.; van de Kerkhof, P.C.M.
Summary: Background: The use of recently introduced biologics targeting specific immune mechanisms has identified crucial steps in the pathogenesis of psoriasis. Studying the dynamics of changes of these target mechanisms in sequential skin biopsies during treatment with biologics may reveal potential biomarkers. Correlation between clinical parameters and the expression of specific genes during treatments may identify markers indicative of treatment response. Objectives: This observational open‐label study aimed to provide an overview of important cell biological changes in lesional skin during treatment with adalimumab, and their relationship to clinical improvement. Methods: Ten patients with moderate‐to‐severe plaque psoriasis were included and treated with adalimumab for 16 weeks. At baseline, and after 10 days and 16 weeks of treatment clinical scores were assessed and biopsies were taken to examine gene expression at the mRNA and protein level. Results: The expression of marker genes for innate immunity, and epidermal differentiation and proliferation was rapidly restored to normal levels, whereas genes of the adaptive immune system showed a delayed decrease. The static and dynamic course of CD1a+ Langerhans cells and Ki67+ nuclei showed a significant strong correlation to the Psoriasis Area and Severity Index score. No correlation between interleukin‐17 expression and clinical scores was found. Conclusions: The innate immune system is affected during adalimumab treatment well before the changes in the adaptive immune system become apparent. We may speculate that the addition of a treatment with an early effect on adaptive immunity to adalimumab may result in superior effectiveness compared with monotherapies.